Whole‐exome sequencing and targeted gene sequencing provide insights into the role of PALB2 as a male breast cancer susceptibility gene. Issue 2 (20th September 2016) - Silvestri, Valentina; Zelli, Veronica; Valentini, Virginia; Rizzolo, Piera; Navazio, Anna Sara; Coppa, Anna; Agata, Simona; Oliani, Cristina; Barana, Daniela; Castrignanò, Tiziana; Viel, Alessandra; Russo, Antonio; et al.
Abstract : BACKGROUND: Male breast cancer (MBC) is a rare disease whose etiology appears to be largely associated with genetic factors. BRCA1 and BRCA2 mutations account for about 10% of all MBC cases. Thus, a fraction of MBC cases are expected to be due to genetic factors not yet identified. To further explain the genetic susceptibility for MBC, whole‐exome sequencing (WES) and targeted gene sequencing were applied to high‐risk, BRCA1/2 mutation–negative MBC cases. METHODS: Germ‐line DNA of 1 male and 2 female BRCA1/2 mutation–negative breast cancer (BC) cases from a pedigree showing a first‐degree family history of MBC was analyzed with WES. Targeted gene sequencing for the validation of WES results was performed for 48 high‐risk, BRCA1/2 mutation–negative MBC cases from an Italian multicenter study of MBC. A case‐control series of 433 BRCA1/2 mutation–negative MBC and female breast cancer (FBC) cases and 849 male and female controls was included in the study. RESULTS: WES in the family identified the partner and localizer of BRCA2 ( PALB2 ) c.419delA truncating mutation carried by the proband, her father, and her paternal uncle (all affected with BC) and the N ‐acetyltransferase 1 ( NAT1 ) c.97C>T nonsense mutation carried by the proband's maternal aunt. Targeted PALB2 sequencing detected the c.1984A>T nonsense mutation in 1 of the 48 BRCA1/2 mutation–negative MBC cases. NAT1 c.97C>T was not found in the case‐control series. CONCLUSIONS: These results add strength to the evidence showing that PALB2 is involved in BC risk for both sexes and indicate that consideration should be given to clinical testing of PALB2 for BRCA1/2 mutation–negative families with multiple MBC and FBC cases. Cancer 2017;123:210–218. © 2016 American Cancer Society . Abstract : This study highlights the important role of partner and localizer of BRCA2 ( PALB2 ) in high‐risk, BRCA1/2 mutation–negative male breast cancer cases and indicates that male breast cancer may be helpful in the identification of PALB2 families. PALB2 seems now to be ready for clinical translation, and families with male breast cancer cases should be considered for PALB2 genetic testing with the aim of improving the clinical management of breast cancer patients and their relatives.